Identification of as a Susceptibility Locus for Kawasaki Disease in Patients Younger than 6 Months of Age - Hea-Ji Kim (Genomics & Informatics, 2018)
Kawasaki disease (KD) is an acute febrile vasculitis predominately affecting infants and children. The dominant incidence age of KD is from 6 months to 5 years of age, and the incidence is unusual in those younger than 6 months and older than 5 years of age. We tried to identify genetic variants specifically associated with KD in patients younger than 6 months or older than 5 years of age. We performed an age-stratified genome-wide association study using the Illumina HumanOmni1-Quad BeadChip data (296 cases vs. 1,000 controls) and a replication study (1,360 cases vs. 3,553 controls) in the Korean population. Among 26 candidate single nucleotide polymorphisms (SNPs) tested in replication study, only a rare nonsynonymous SNP (rs4365796: c.1106C＞T, p.Thr369Met) in the lymphoid enhancer binding factor 1 (LEF1) gene was very significantly associated with KD in patients younger than 6 months of age (odds ratio [OR], 3.07; pcombined = 1.10 × 10-5), whereas no association of the same SNP was observed in any other age group of KD patients. The same SNP (rs4365796) in the LEF1 gene showed the same direction of risk effect in Japanese KD patients younger than 6 months of age, although the effect was not statistically significant (OR, 1.42; p = 0.397). This result indicates that the LEF1 gene may play an important role as a susceptibility gene specifically affecting KD patients younger than 6 months of age.